Chronic Spinal Pain and Financial Worries in the US Adult Population. Issue 8 (15th April 2020) - Yang, Haiou; Haldeman, Scott
Abstract : Study Design: Epidemiological study based on cross-sectional data of a representative sample. Objective: To determine whether financial worries are associated with chronic spinal pain in the US adult population. Summary of Background Data: This study used data from the US 2015 National Health Interview Survey. The sample size was 33, 672 and the study population is defined as aged 18 to 85 years. Methods: To account for the complex sampling design, the Taylor linearized variance estimation method was used. Spinal pain was defined in two ways: chronic low back pain and neck pain, chronic low back pain and/or neck pain. Eight types of financial worries were assessed: paying monthly bills, maintaining standard of living, credit card payments, paying rent/mortgage/housing costs, medical costs for healthcare, money for retirement, medical costs of illness/accident, and paying for children's college. Results: Different types of financial worries were significantly associated with chronic spinal pain, controlling for demographic characteristics and socioeconomic status. These worries included paying monthly bills (odds ratio [OR] 2.5), maintaining standard of living (OR 2.5), credit card payments (OR 2.2), paying rent/mortgage/housing costs (OR 2.2), medical costs for healthcare (OR 2.2), money for retirement, (OR 2.3), medical costs of illness/accident (OR 2.2), and paying for children's college (OR 1.4). Conclusion: This study shows that financial worries were significantly associated with chronic spinal pain. Financial worries may be important to be taken into consideration by clinicians managing patients with spinal pain. More future research is needed to explore the association between financial worries and spinal pain. Level of Evidence: 3 Abstract : This study is an epidemiological study based on data from the 2015 National Health Interview Survey with a representative sample of the US adult population. This study suggests that financial worries may have an association with chronic spinal pain and should be taken into consideration by clinicians managing patients with spinal pain.